2021
DOI: 10.1111/nmo.14274
|View full text |Cite
|
Sign up to set email alerts
|

Baseline predictive factors for foregut and hindgut response to long‐term gastric electrical stimulation using augmented energy

Abstract: Introduction: Gastric electrical stimulation (GES) has been recommended for drug refractory patients with gastroparesis, but no clear baseline predictors of symptom response exist. We hypothesized that long-term predictors to GES for foregut and hindgut symptoms exist, particularly when using augmented energies. Patients:We evaluated 307 patients at baseline, 1 week post temporary GES, and one year after permanent GES. Baseline measures included upper and lower symptoms by patient-reported outcomes (PRO), soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This uses a 0-4 scale from (0=low, 4=high) 9,10 . The Lower GI and GU data were examined and recently-published work has shown that hindgut function can be a predictor of response to GES 11 …”
Section: Methodsmentioning
confidence: 99%
“…This uses a 0-4 scale from (0=low, 4=high) 9,10 . The Lower GI and GU data were examined and recently-published work has shown that hindgut function can be a predictor of response to GES 11 …”
Section: Methodsmentioning
confidence: 99%
“…Based on current practice, many patients end up with settings of about 15 milliamps with 2 seconds on and 3 seconds off. [ 9 ]…”
Section: Ges Methodsmentioning
confidence: 99%
“…Other subtypes of Gp have not been as well studied but some predictors of response to GES, including low BMI and the presence of hindgut symptoms, have recently been described. [9] Some patients receive GES off-label use of GES for post-surgical Gp symptoms, and who may or may not have delayed solid gastric emptying on testing. Other patients have symptoms of Gp but with non-delayed solid gastric emptying-the so called gastroparesis-like syndrome (GLS) or severe functional dyspepsia (FD)may receive GES devices, particularly if they respond to a trial of temporary GES.…”
Section: Indications For Gesmentioning
confidence: 99%
See 1 more Smart Citation